The Cro-Magnon babies: Morphology and mortuary implications of the Cro-Magnon immature remains. (April 2020) - Partiot, Caroline; Trinkaus, Erik; Knüsel, Christopher J.; Villotte, Sébastien
Highlights: There are at least 4 individuals who died before 1 year of age at Cro-Magnon. Most remains fit within the variation of the recent and Late Pleistocene samples. The demographic profile of the site is unusual in the Gravettian context. The demographic profile of the site suggests selective funerary practices. Abstract: Although the adult skeletons discovered in 1868 at the Cro-Magnon site (Dordogne, France) have been studied several times, the immature remains known as Cro-Magnon 5 and exhumed at the same time were only analyzed in detail once, some thirty years ago. Since then, doubts have persisted concerning, in particular, the minimum number of immature individuals present in the assemblage. A re-analysis of these immature remains (cranial fragments and long bone diaphyses) documents the presence of three neonates and one older infant in the sample. They are morphologically and metrically similar to recent and Late Pleistocene modern human infants, although the metaphyses of one femur are modestly unusual. They also document an unusual mortuary age profile at Cro-Magnon, with four infants, three older adults, and an additional adult, which raises questions about the manner of selection of individuals deposited in the Cro-Magnon rock-shelter.